Bacillus subtilis phenylalanyl-tRNA synthetase genes: cloning and expression in Escherichia coli and B. subtilis. - Brakhage, A A (1989)
The genes that encode the two subunits of Bacillus subtilis phenylalanyl-tRNA synthetase were cloned from alpha lambda library of chromosomal B. subtilis DNA by specific complementation of a thermosensitive Escherichia coli pheS mutation. Both genes (we named them pheS and pheT, analogous to the corresponding genes of E. coli) are carried by a 6.6-kilobase-pair PstI fragment which also complements E. coli pheT mutations. This fragment directs the synthesis of two proteins identical in size to the purified alpha and beta subunits of the phenylalanyl-tRNA synthetase of B. subtilis with Mrs of 42,000 and 97,000, respectively. A recombinant shuttle plasmid carrying the genes caused 10-fold overproduction of functional phenylalanyl-tRNA synthetase in B. subtilis.